2019
DOI: 10.1186/s12967-019-1806-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and phosphorylation of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase isoforms in urinary exosomes in pre-eclampsia

Abstract: Background Glycolysis is altered in various kidney diseases, but little is known about glycolysis in pre-eclampsia, a multi-system disorder with major pathological effects on the kidney. Urinary exosomes provide a non-invasive alternative for studying changes in kidney metabolism. This study aims to characterise the expression and phosphorylation of isozymes of the key glycolytic regulatory protein, 6-phosphofructokinase-2-kinase/fructose-2,6-bisphosphatase (PFK-2/FBPase-2), in urinary exosomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…It has been reported that the phosphorylation of PFKFB2 is critical for its activation. 16) Consistently, compared with the control groups, the MIpost mice demonstrated remarkably elevated phosphorylation levels of PFKFB2 in cardiac tissues ( Figure 1B). The IHC staining further revealed that the protein expression of PFKFB2 was increased in the peri-infarct region of heart tissues from the MI mice ( Figure 1C), suggesting that PFKFB2 may be closely correlated with the development of MI.…”
Section: Resultssupporting
confidence: 60%
“…It has been reported that the phosphorylation of PFKFB2 is critical for its activation. 16) Consistently, compared with the control groups, the MIpost mice demonstrated remarkably elevated phosphorylation levels of PFKFB2 in cardiac tissues ( Figure 1B). The IHC staining further revealed that the protein expression of PFKFB2 was increased in the peri-infarct region of heart tissues from the MI mice ( Figure 1C), suggesting that PFKFB2 may be closely correlated with the development of MI.…”
Section: Resultssupporting
confidence: 60%
“…PFKFB3 facilitates the allosteric activation of PFK‐1 through the production of F‐2,6‐BP, thereby accelerating glycolytic flux. A prior study confirmed that PFKFB3 protein expression and phosphorylation were relatively elevated in urinary exosomes isolated from preeclamptic patients 164 . Subsequently, researchers investigated the mechanism of PFKFB3 in preeclampsia.…”
Section: Glycolysis In Pathological Pregnancymentioning
confidence: 89%
“…So far, the only and most reliable treatment for PE is delivery, but the pathogenesis of PE is still an enigma. About the pathogenesis, two-stage theory is now widely accepted: In stage I, during embryogenesis, trophoblast invasion of the uterine myometrium is inadequate and the uterine spiral artery remodeling is impaired, which leads toplacental ischemia and hypoxiametabolism disorder; In stage II, the presence of a large number of undesirable factors in the maternal blood leads to a systemic inflammatory response and vascular endothelial dysfunction in the maternal body, which eventually results in PE (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%